2005
DOI: 10.1002/cncr.21378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nuclear score for p16INK4a-stained cervical squamous cells in liquid-based cytology samples

Abstract: The 546‐base pair enhancer of limb expression HACNS1, which is highly constrained in all terrestrial vertebrates, has accumulated 16 human‐specific changes after the human‐chimpanzee split. There has been discussion whether this process was driven by positive selection or biased gene conversion, without considering population data. We studied 83 South Amerindian, 11 Eskimo, 35 Europeans, 37 Bantu, and non‐Bantu Sub‐Saharan speakers, and 28 Brazilian mestizo samples and found no variation in this DNA region. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 73 publications
2
95
1
Order By: Relevance
“…34 Based on our results, it is very well conceivable that the detection of p16 INK4a -positive cells that simultaneously coexpress Ki-67 within the same cell in cervical cytology preparations may identify cervical epithelial cells with deregulated cell cycle control mediated by HR-HPV oncogene expression and thus may be indicative of cervical dysplasia. The presented data strongly suggest that the immunohistochemical staining for p16…”
Section: Immunohistochemical Staining For P16mentioning
confidence: 57%
“…34 Based on our results, it is very well conceivable that the detection of p16 INK4a -positive cells that simultaneously coexpress Ki-67 within the same cell in cervical cytology preparations may identify cervical epithelial cells with deregulated cell cycle control mediated by HR-HPV oncogene expression and thus may be indicative of cervical dysplasia. The presented data strongly suggest that the immunohistochemical staining for p16…”
Section: Immunohistochemical Staining For P16mentioning
confidence: 57%
“…A previous p16 assay required morphologic evaluation of p16-stained cells to discriminate HPVtransformed cells from metaplastic cells. 8 To improve specificity and to reduce subjectivity, the proliferation marker Ki-67 was added to the assay. The test is considered positive when staining for both p16 and Ki-67 is observed in the same cell, obviating the need for morphologic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The p16 ink4a overexpression is an indicator of aberrant expression of viral oncogenes and HPV-induced transformation of epithelial cells [10]. Several research groups (including us) have demonstrated by immunohistochemical technique a manifold increase of the p16 ink4a expression in cervical dysplasia and carcinomas in comparison with that in normal epithelium [16][17][18][19] There is an abundant evidence demonstrating that immunohisto-/cytochemical detection of the protein p16 ink4a is a promising test for revealing the HPV-infected cells with malignant potential [ [10,20], for review see [21]]. Thus, the detection of the protein p16 ink4a overexpression is especially useful for early diagnostics of HR-HPV-associated cervical cancer.…”
Section: Introductionmentioning
confidence: 99%